2021
DOI: 10.1002/tox.23138
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of mesoporous silica modified by amino and carboxyl groups on vascular endothelial cells

Abstract: Mesoporous silica is widely used because of its unique and excellent properties, especially it can be used as a drug carrier and gene carrier in the biomedical field. After the mesoporous silica is put into clinical use, it is more likely to be exposed in human body. Therefore, the effect of mesoporous silica on human body cannot be ignored. The injury of vascular endothelial cells is a prerequisite for the occurrence of many cardiovascular diseases. As a drug and gene carrier, mesoporous silica increases its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The results showed no statistical difference comparing the control and the nanosystem, corroborating that SBA-15/HAP_2 has no cytotoxicity at the dose of 20 µg/mL in HU-VEC cells. These data are corroborated by Gonzalez et al [52]. In their study, they used SBA-15 capped with hydroxyapatite and demonstrated a non-toxic effect on cells.…”
Section: Immunoblottingsupporting
confidence: 71%
See 1 more Smart Citation
“…The results showed no statistical difference comparing the control and the nanosystem, corroborating that SBA-15/HAP_2 has no cytotoxicity at the dose of 20 µg/mL in HU-VEC cells. These data are corroborated by Gonzalez et al [52]. In their study, they used SBA-15 capped with hydroxyapatite and demonstrated a non-toxic effect on cells.…”
Section: Immunoblottingsupporting
confidence: 71%
“…Chen Ying et al [ 51 ] showed that mesoporous silica capped with hydroxyapatite has excellent biocompatibility and may serve as a drug delivery system without influencing cell proliferation. Controversially, Zhao et al [ 52 ], using SBA-15 in three forms (SBA-15, NH2-SBA-15, and COOH-SBA-15), demonstrated that pure SBA-15 is the highest cytotoxic form for HUVEC cells. They also revealed that the carboxyl-modified group (COOH-SBA-15) reduced the cytotoxicity of the SBA-15 by reducing the oxidative stress, and this fact can partially explain the absence of cytotoxicity in the SBA-15/HAP_2 sample.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we can assume that the powders obtained by us can be used safely, probably due to their particle size, which varies from 160 to 850 nm. Moreover, Zhao et al showed that modified nanosilica was less toxic to endothelial cells than unmodified [49]. This report showed that the introduction of amino and carboxyl groups on 15-nm silica grains resulted in a significant reduction in toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…COOH-SBA-15 was the lowest. 168 However, whether derivatized or not, all SiO 2 particles induced oxidative and cell membrane damage.…”
Section: Carboxylic Groups and Cytotoxic Studiesmentioning
confidence: 99%